2020
DOI: 10.1039/d0ra03871g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steam de-alumination on the interactions of propene with H-ZSM-5 zeolites

Abstract: Inelastic and quasi-elastic neutron scattering are used to investigate how steaming changes the physico-chemical characteristics of the zeolite ZSM-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 59 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…S4), with P/mesoZ30-ss and P/mesoZ55-ss showing 1% and 2% lower crystallinity than P/mesoZ30 and P/mesoZ55 according to the integrated peak areas in the range of 22.5-25.0 • 2θ (ASTM D 5758 -01). Generally, the crystallinity is not affected by steaming at moderate temperatures of 29 Si MAS NMR peak simulations; f from Pyridine-IR, baseline-to-baseline integration of 1545 cm − 1; g from Pyridine-IR, baseline-to-baseline integration of 1455 cm − 1 ; 450-650 • C while a severe decrease in acidity results [66][67][68]. After steaming at 800 • C, decreases in crystallinity to 90-95% of the crystallinity determined for the P-modified sample were reported by other researchers [53,69].…”
Section: Catalyst Propertiesmentioning
confidence: 99%
“…S4), with P/mesoZ30-ss and P/mesoZ55-ss showing 1% and 2% lower crystallinity than P/mesoZ30 and P/mesoZ55 according to the integrated peak areas in the range of 22.5-25.0 • 2θ (ASTM D 5758 -01). Generally, the crystallinity is not affected by steaming at moderate temperatures of 29 Si MAS NMR peak simulations; f from Pyridine-IR, baseline-to-baseline integration of 1545 cm − 1; g from Pyridine-IR, baseline-to-baseline integration of 1455 cm − 1 ; 450-650 • C while a severe decrease in acidity results [66][67][68]. After steaming at 800 • C, decreases in crystallinity to 90-95% of the crystallinity determined for the P-modified sample were reported by other researchers [53,69].…”
Section: Catalyst Propertiesmentioning
confidence: 99%
“…The key challenge for light alkane conversion under anaerobic conditions is the activation of inert C–H bonds at low temperatures and avoid the ubiquitous coke deposition at high temperatures. To mitigate these challenges, H 2 , H 2 O (g), and CO 2 have been frequently employed as auxiliary reactants during dehydrogenation and aromatization. , However, the use of H 2 as an auxiliary gas will decrease the equilibrium conversion of dehydrogenation and aromatization, and the presence of H 2 O (g) and CO 2 (presence of CO 2 could result in H 2 O (g) formation) has the potential risk of de-alumination of zeolites at high temperatures …”
Section: Introductionmentioning
confidence: 99%
“…25,26 However, the use of H 2 as an auxiliary gas will decrease the equilibrium conversion of dehydrogenation and aromatization, and the presence of H 2 O (g) and CO 2 (presence of CO 2 could result in H 2 O (g) formation) has the potential risk of de-alumination of zeolites at high temperatures. 27 Alternative to H 2 , H 2 O (g), and CO 2 , we suggested using NH 3 as an auxiliary gas or reactant for light alkane conversion. While the original idea is to tune catalyst coke resistibility during ethane aromatization, the results demonstrated that completely different products were formed when coprocessing ethane and NH 3 under the same reaction conditions of ethane The carbon-based product from ethane ADeH is similar to the conventional ammoxidation, 29 which also aims at CH 3 CN production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zeolites have been extensively used across a wide variety of industrial applications, ranging from chemical synthesis, adsorbents, and molecular sieves. In the context of catalytic conversions, aluminosilicate zeolites such as ZSM-5 have been commonly used as solid acid catalysts for a wide range of chemistries. , Among the various chemistries, biomass upgrading over zeolites has received significant attention as a sustainable and alternative route to chemical production. Biomass catalytic upgrading strategies typically involve dehydration, decarboxylation, and aldol condensation. However, relative to petrochemical conversion strategies, the inherently higher water content of biomass poses a challenge, where its presence in the pores of a zeolite can significantly alter catalytic chemistries and kinetics. , The impact of water on a zeolite-catalyzed chemistry has led to numerous investigations into the origin of the effect of water on the catalytic process that leads to a change in reaction rates and selectivities. , Major effects of water on the catalytic reactions include adsorption on active sites, solvation of reactants, and transition states . Understanding the catalytic consequence of solvent environments like the aqueous phase is therefore central to designing solid acids for biomass catalytic upgrading strategies.…”
Section: Introductionmentioning
confidence: 99%